1974
DOI: 10.1002/1097-0142(197404)33:4<959::aid-cncr2820330410>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Serum alpha-fetoprotein in 184 ugandan patients with hepatocellular carcinoma.Clinical, laboratory, and histopathologic correlations

Abstract: Qualitative serum alpha‐fetoprotein (AFP) determinations were done on sera from 184 Ugandan patients with hepatocellular carcinoma (HC) and the results correlated with clinical, laboratory, and histopathologic features of the disease. One hundred twenty‐one (66%) were AFP positive. Young patients and those with concomitant hepatitis B antigenemia (HBAg) were AFP positive significantly more frequently than older and HBAg negative patients. There were no differences in AFP frequency between patients with or with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
2

Year Published

1975
1975
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 20 publications
(1 reference statement)
0
6
0
2
Order By: Relevance
“…The correlation between AFP level and grade of tumor cell differentiation has been reported incoherently. Some reports showed that the presence of AFP tended to correlate with poorly differentiated HCC or high grade HCC,28, 30, 31 whereas other reports revealed no correlation between AFP level and tumor grade 32, 33. Conversely, two reports stated that patients with both Grade 1 and Grade 4 HCC were associated with lower serum AFP levels 34, 35.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between AFP level and grade of tumor cell differentiation has been reported incoherently. Some reports showed that the presence of AFP tended to correlate with poorly differentiated HCC or high grade HCC,28, 30, 31 whereas other reports revealed no correlation between AFP level and tumor grade 32, 33. Conversely, two reports stated that patients with both Grade 1 and Grade 4 HCC were associated with lower serum AFP levels 34, 35.…”
Section: Discussionmentioning
confidence: 99%
“…Further, alpha-fetoprotein is shown in this study to be less sensitive and of inferior accuracy in the diagnosis of HCC when compared with DCP for patients presenting with tumour size ≥3 cm. The sensitivity of 62.8 % is lower than 83.7 % reported in 1988 in South Africa [ 13 ] 66 percent in 1974 in Uganda, [ 33 ] and 90 % in 1992 in Zaire [ 34 ]. This may partly be due to the fact that some of the studies were done using immuno - diffusion method rather than radioimmunoassay and enzyme immunoassay.…”
Section: Discussionmentioning
confidence: 67%
“…A correlation has been found to exist between HBsAg positivity and serum AFP levels in HCC patients. HCC patients who are positive for HBsAg are significantly more likely to be AFP positive and have higher levels of AFP than those who are not, suggesting a relationship between HBV infection and AFP production [ 27 , 33 , 40 ]. Similarly, DCP has also been reported to perform better in those with viral aetiology [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, there appears to be no significant difference in survival between serum AFP-positive and negative patients. 29 Our tumors containing IHG have mostly been well to moderately differentiated; the five from patients with positive serum AFP were all moderately well-differentiated. T h e globules in liver cells of Pi-type ZZ alpha-1-antitrypsin deficient patients with concomitant primary liver cell carcinomas may render the hepatocytes susceptible to injury by additional factors ultimately resulting in hepatic fibrosis, cirrhosis, and malignant he pa to ma^.^^'^ Whether the IHG noted in the tumor cells of hepatocellular carcinomas are of importance in carcinogenesis and whether they will assist in the assessment of prognosis remains to be seen.…”
Section: Discussionmentioning
confidence: 84%